Mitotically Active Sclerosing Stromal Tumor of the Ovary: Report of a Case Series With Parallels to Mitotically Active Cellular Fibroma. (November 2016) - Goebel, Emily A.; McCluggage, W. Glenn; Walsh, Joanna C.
Abstract : Sclerosing stromal tumor of the ovary is a rare neoplasm that typically occurs in the second and third decades of life. To date, all reported cases have behaved in a benign manner. In their usual form, these neoplasms exhibit scant, if any, mitotic activity. Herein, we report a case series of 6 sclerosing stromal tumors with increased mitotic activity (between 7 and 12 mitoses per 10 high-power fields in the most mitotically active areas). Follow-up is available in 4 of 6 cases (ranging from 3 wk to 68 mo) and 1 tumor recurred within the pelvis. We suggest that the term mitotically active sclerosing stromal tumor is used for such neoplasms and draw parallels with mitotically active cellular fibroma, another benign ovarian stromal neoplasm which occasionally recurs locally, but which does not metastasize.